Efficacy and Safety of Intralesional Vitamin D3 Injection in Recalcitrant Periungual Warts: A Randomized Controlled Trial - Khan, Md Shirajul Islam; Khan, Usama Salman (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Although the treatment of recalcitrant warts is often disappointing due to its high recurrence rates, the intralesional injections of Vitamin D3 (as an immunotherapeutic molecule) may regulate epidermal cell proliferation. Objective: To evaluate whether intralesional vitamin D3 immunotherapy is efficient and secure in treating the recalcitrant periungual warts. Materials and Methods: This randomized controlled therapeutic trial was performed in the Department of Dermatology and Venereology of Combined Military Hospital, Dhaka from July 2018 to December 2019. A total of 64 participants’ having different sizes and duration of recalcitrant periungual warts were included. Half of them were injected with about 0.2ml vitamin D3 solution (600,000 IU, 15 mg/ml) at the base of the wart (Group-A) and the remaining participants were subjected to cryotherapy (Group-B). A follow-up period of 6 months following the last session was performed to detect any recurrence. Results: The mean age of participants in Group A and B were 25.9±12.6 and 26.4±12.4 years, respectively (78.1% male in Group-A and 62.5% in Group B). The size and duration of warts between the two groups were not statistically significant (p>0.05). The treatment outcome in Group-A varied from excellent 19(59.4%) to significant 8(25.0%), moderate 3(9.4%), mild (3.1%), and no response 1(3.1%), whereas in Group-B, the results were as follows: excellent 13(40.6%), significant 3(9.4%), moderate 9(28.1%), mild 7(21.9%). The efficacy was significantly higher in Group-A when compared to Group-B (p <0.05). Furthermore, the burning sensation, blister, erythema, hypopigmentation, depigmentation and skin atrophy were significantly higher in Group-B compared to Group-A. The recurrence of warts were 12.5% and 34.4% in Group-A and B respectively. Conclusion: Vitamin D3 injection is more effective and secure than cryotherapy in the treatment of periungual warts. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 3-6